The economic valuation of the convenience of using disposable takeaway containers in Singapore: a contingent valuation approach - Tan, Michelle Xin Yi (Nanyang Technological University, 2024)
The increasing reliance on takeaway food, as a result of Singaporeans’ hectic lifestyles, has led to a significant use of single-use plastic containers. The excessive use of plastics is not only detrimental to our environment but also placing strain on our sole landfill. To avert this crisis and encourage the use of reusable food containers, this study aims to estimate Singaporean residents’ willingness-to-pay (WTP) for the convenience of using takeaway containers through a Contingent Valuation approach. This study also seeks to incorporate a psychological prime to stimulate environmental consciousness, with the intention of examining its impact on WTP. In a demographically stratified sample of 400 Singapore residents, it is found that the average Singaporeans’ WTP for the intrinsic value placed on convenience is $0.39 per container. An analysis of the Probit regression uncovered that age and the frequency of bringing reusable containers have a significant effect on WTP. Additionally, the visual prime effectively influenced people to adopt environmentally conscious attitudes, giving a WTP of $0.50, which is lower than the non-prime which gave a WTP of $0.55. This study's results could shape pricing policies, regulations on takeaway containers, and initiatives to cut plastic usage in Singapore.